2019
DOI: 10.2478/sjecr-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Chronic Administration of DPP4-Inhibitors on Systemic Oxidative Stress in Rats with Diabetes Type 2

Abstract: Type 2 diabetes (T2DM) is characterized by well-preserved insulin secretion; however, the surrounding tissue is insensitive to insulin, resulting in increased blood glucose level due to the inability of tissues to convert glucose into energy. As a result of chronic non-regulation of glucose levels and high daily fluctuations in the blood, the micro- and macrovascular complications occur in these patients. Complications develop through two main mechanisms: induction of oxidative stress and innate immunity. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(45 reference statements)
3
1
0
Order By: Relevance
“…These results align well with another study by Marques et al, 2019 in which Sitagliptin treatment ameliorated renal oxidative stress in rats with diabetes (Marques et al, 2019). Another study highlighted the anti-oxidant potential of gliptins, similar to this study (Bolevich et al, 2019). (Matsui, Nishino, Takeuchi, & Yamagishi, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…These results align well with another study by Marques et al, 2019 in which Sitagliptin treatment ameliorated renal oxidative stress in rats with diabetes (Marques et al, 2019). Another study highlighted the anti-oxidant potential of gliptins, similar to this study (Bolevich et al, 2019). (Matsui, Nishino, Takeuchi, & Yamagishi, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Saxagliptin and Pioglitazone appear to have a synergistic effect on lipid profile improvement, as the best results were observed in the group that received combination therapy. In line with our findings, Saxagliptin was reported to improve dyslipidemia [45]. Pioglitazone has also been shown to improve lipid profiles [46].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding oxidative stress, the effect of DPP-4 inhibitors and TZDs has been previously studied individually. One animal study reported similar results to our experiment, where three DPP-4 inhibitors, namely Saxagliptin, Sitagliptin, and Vildagliptin, were found to significantly reduce oxidative stress in STZ-induced diabetic rats [45]. Meanwhile, in a 16week clinical trial involving 40 patients with advanced diabetic nephropathy, Pioglitazone did not affect reducing oxidative stress [47].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation